C/EBPβ deficiency enhances keratinocyte apoptosis after UVB-induced DNA damage via regulation of the type I IFN and TNF responses - Tobin, Emma E.; Sharma, Ayushma; Kros, Samantha T.; Jima, Dereje D.; Gray, Sophia C.; Hall, Jonathan R. (Frontiers in Cell Death, 2025)
The epidermis is routinely subjected to DNA damage induced by ultraviolet B (UVB) solar radiation. In addition to activating canonical DNA damage responses such as cycle cell checkpoints and DNA repair, UVB-induced DNA damage can also activate additional signaling pathways including inflammatory responses. The pathways activated downstream of UVB-induced DNA damage have a critical role in determining cellular survival to UVB radiation. Here we report that loss of CCAAT/enhancer binding protein β (C/EBPβ) in mouse keratinocytes results in enhanced UVB-induced apoptosis through activation of extrinsic apoptosis genes cleaved caspase-8 and truncated BH3 interacting-domain death agonist (tBid). RNAseq and Ingenuity Pathway Analysis of UVB-treated C/EBPβ−/− primary keratinocytes revealed an enrichment of inflammatory signaling pathways, including the type I interferon (IFN-I) pathway as the most enriched pathway. Numerous IFN-I stimulated genes were up-regulated in UVB-treated C/EBPβ−/− keratinocytes, including genes that regulate extrinsic apoptosis. Inhibition of the interferon-α/β receptor or the associated kinase Tyk2 greatly reduced cell death in UVB-exposed C/EBPβ deficient keratinocytes, demonstrating the dependence of IFN signaling in C/EBPβ regulated apoptosis. The apoptosis inducing cytokine tumor necrosis factor alpha (TNF-α) was identified as one of the most significant upstream regulators activated in UVB-exposed C/EBPβ−/− keratinocytes compared to UVB exposed wild type control. UVB-exposed C/EBPβ−/− keratinocytes displayed increased expression of TNF-α and the enhanced apoptosis in C/EBPβ−/− keratinocytes was suppressed by a TNF-α neutralizing antibody. Our results indicate that loss of C/EBPβ enhances activation of a non-canonical UVB DNA damage response pathway involving interferon and TNF signaling to induce keratinocyte cell death.